Genetics of animal health - Berry, Donagh (Henry Stewart Talks, 2013)
Importance of genetic of animal health, Heritability, Phenotype as a function of genetics & environment, Genetic gain, Health traits, Viral diseases, Udder traits: genetic variation across species, Lameness (cattle & sheep), Bacterial diseases, Fertility traits (dairy cows), Metabolic diseases, Parasites, Genetic trends, Somatic cell score, Mastitis and other diseases, Genetic correlations between traits, Increase accuracy of selection, Predictor traits, Indirect selection, New technologies (genomics and others), Genome wide association studies and enabled selection